2021
DOI: 10.3390/jcm10091895
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Social Activities and Relationship between Walking Habits and Disability Incidence

Abstract: Identifying the relationship between physical and social activity and disability among community-dwelling older adults may provide important information for implementing tailored interventions to prevent disability progression. The aim of this study was to determine the effect of the number of social activities on the relationship between walking habits and disability incidence in older adults. We included 2873 older adults (mean age, 73.1 years; SD, ±5.9 years) from the National Center for Geriatrics and Gero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Dimension 2 (ego centrality or social integration) as Dimension 3 (strengths of contacts or social support) was only linked to the number of people living with ego. This last result is logical and has been found in many studies (Hsieh & Zhang, 2021;Katayama et al, 2021;Lowndes et al, 2021;Seeman & Berkman, 1988;Zainuddin et al, 2020), but we expected to observe other influences, such as those from income, population density, urban quality, and accessibility (Kim et al, 2018;Sharmeen et al, 2014). Wood et al (2010) for example, studied the association between sense of community, walking, and neighborhood design characteristics and found that the sense of community was enhanced by living in areas that encourage leisurely walking.…”
Section: Discussionsupporting
confidence: 53%
“…Dimension 2 (ego centrality or social integration) as Dimension 3 (strengths of contacts or social support) was only linked to the number of people living with ego. This last result is logical and has been found in many studies (Hsieh & Zhang, 2021;Katayama et al, 2021;Lowndes et al, 2021;Seeman & Berkman, 1988;Zainuddin et al, 2020), but we expected to observe other influences, such as those from income, population density, urban quality, and accessibility (Kim et al, 2018;Sharmeen et al, 2014). Wood et al (2010) for example, studied the association between sense of community, walking, and neighborhood design characteristics and found that the sense of community was enhanced by living in areas that encourage leisurely walking.…”
Section: Discussionsupporting
confidence: 53%
“…In relation to the present work, a previous study found that the perception of psychological well-being and the improvement of subjective health were also significantly related to regular and intensive physical exercise [ 52 ], another recent study indicates that daily physical activity has psycho-social benefits in the older adults and may lead to better outcomes in the primary prevention of disability [ 53 ]. The improvements reported by the experimental group coincide with those of other aquatic training programs developed in older adults, who also obtained improvements in functional autonomy [ 54 ], although in their case, they did not carry out psychological strategies.…”
Section: Discussionmentioning
confidence: 64%
“…We believe the explanation for these findings is that both of these types of activities require physical exercise. Researchers found that walking was beneficial to older people's physical performance (Katayama et al, 2021;Wong et al, 2003), which could include decreasing their eventual need for long-term care/support.…”
Section: Discussionmentioning
confidence: 99%